2013
DOI: 10.2308/acch-50434
|View full text |Cite
|
Sign up to set email alerts
|

Capital Structure, Earnings Management, and Sarbanes-Oxley: Evidence from Canadian and U.S. Firms

Abstract: SYNOPSIS I examine Sarbanes-Oxley's (SOX) effect on capital structure. I find that SOX is associated with higher long-term debt ratios, as firms listed in the U.S. raise their long-term debt ratios by 2 to 3 percentage points. This finding is consistent with the idea that, although the reduction in information asymmetry associated with SOX could prompt managers to increase equity financing, debt is still safer and less costly than equity in the SOX era. Further analysis shows that the increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…Notice that our results add to the understanding of a specific benefit of the Sarbanes‐Oxley Act. Like Carter () and Andrade et al (), we found a positive effect of SOX on terms of credit. Our model shows that the effect of SOX comes from a reduction in the information asymmetry between borrowers and lenders, mainly through three channels: disclosure, monitoring, and manager punishment.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…Notice that our results add to the understanding of a specific benefit of the Sarbanes‐Oxley Act. Like Carter () and Andrade et al (), we found a positive effect of SOX on terms of credit. Our model shows that the effect of SOX comes from a reduction in the information asymmetry between borrowers and lenders, mainly through three channels: disclosure, monitoring, and manager punishment.…”
Section: Resultssupporting
confidence: 86%
“…For example, Litvak () compares returns to cross‐listed companies subject to SOX (cross‐listed at level 2 or 3) to returns of matching non‐cross‐listed companies from the same industry and country and similar in size. Carter () uses Canadian firms to examine the effect of SOX on long‐term debt ratios. Costello and Wittenberg‐Moerman () rely on SOX's internal control reports to measure financial reporting quality.…”
Section: Empirical Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior research also finds that IPO underpricing generally decreases after SOX (e.g., Johnston & Madura, ). Carter () shows that information asymmetry decreases and long‐term debt ratio increases after SOX for mature firms. Johnston and Madura () find that the decreased information asymmetry after SOX is related with lower IPO underpricing for newly listed firms.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%